Trades access common core. Line B, Employability skills, Competency B-2, Describe expectations and responsibilities of employers and employees - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"As you enter the workforce, it is important to understand the major trends in employment and how to find this information. In this Competency, we'll look some of the current major trends in employment in Canada and British Columbia. This review includes an overview of the economy, skills that employers look for, and employee expectations. We'll also look at employee expectations and effective strategies for entering the labour market and finding a job. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line B - Employability Skills. B-1 Apply Study and Learning Skills, B-2 Describe Expectations and Responsibilities of Employers and Employees, B-3 Use Interpersonal Communication Skills, B-4 Describe the Apprenticeship System."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Industrial relations -- Textbooks; Employability -- Textbooks; Electronic books